2012
DOI: 10.1055/s-0031-1298240
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Discrimination of Rhizoma Coptidis from Different Species Using1H NMR Spectroscopy and Principal Component Analysis

Abstract: Rhizoma coptidis, a broadly used medicinal plant, originates from the dried rhizomes of three species in Chinese pharmacopoeia, namely, Coptis chinensis Franch, Coptis deltoidea C. Y. Cheng et Hsiao, and Coptis teeta Wall. In this study, a novel approach using (1)H NMR spectroscopy combined with multivariate analysis was introduced to differentiate the three species and identify potential metabolic markers for better controlling the quality of rhizoma coptidis. A broad range of metabolites including alkaloids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Quantitative 1 H-NMR (qH-NMR) has been widely used for the analysis of bioactive components in complex plant extracts in recent years [ 54 56 ]. qH-NMR has shown some advantages for quantitative analysis over traditional chromatographic methods, such as simple and easy sample preparation and handling, lower reagent consumption, elimination of the need of expensive standard compounds, and shorter analysis time.…”
Section: Quality Evaluation Of Crmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative 1 H-NMR (qH-NMR) has been widely used for the analysis of bioactive components in complex plant extracts in recent years [ 54 56 ]. qH-NMR has shown some advantages for quantitative analysis over traditional chromatographic methods, such as simple and easy sample preparation and handling, lower reagent consumption, elimination of the need of expensive standard compounds, and shorter analysis time.…”
Section: Quality Evaluation Of Crmentioning
confidence: 99%
“…qH-NMR has shown some advantages for quantitative analysis over traditional chromatographic methods, such as simple and easy sample preparation and handling, lower reagent consumption, elimination of the need of expensive standard compounds, and shorter analysis time. Because the C13-H signals of the main alkaloids in 1 H NMR can be easily distinguished from each other, the quantitative determination of the main alkaloids from CR could be achieved by qH-NMR and the 3 species of CR could also be differentiated by 1 H NMR and principal component analysis [ 3 , 56 58 ].…”
Section: Quality Evaluation Of Crmentioning
confidence: 99%
“…These constituents display many medicinal properties such as antiviral, anti-inflammatory and antimicrobial activities [16,17,18]. In recent years, many analytical methods including high performance liquid chromatography-ultraviolet (HPLC-UV), ultra-performance liquid chromatography (UPLC) and proton nuclear magnetic resonance ( 1 H-NMR) have been used to analyze these compounds in Coptis plants [19,20,21]. These studies have shown that their contents are obviously different among different species.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Up to now, quite a few approaches have been reported regarding alkaloid analyses in CR. [35][36][37][38][39][40][41][42][43][44][45][46] However, most analyses concerned the alkaloids in either raw materials or specific extracts, but not the distribution in tissues and cells. To our knowledge, histochemical studies of CR for its quality evaluation are rarely found, so CR was set as an example to carry out the study of CMM from different growing areas, focusing on bioactive constituents with their distribution and accumulation rules in anatomical sections.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Hong Kong Chinese Materia Medica Standards and the Chinese Pharmacopeia have also chosen the alkaloids as the major bioactive components to evaluate the quality of this CMM . Up to now, quite a few approaches have been reported regarding alkaloid analyses in CR . However, most analyses concerned the alkaloids in either raw materials or specific extracts, but not the distribution in tissues and cells.…”
Section: Introductionmentioning
confidence: 99%